Fate of Dissolved Organic Matter and Cooperation Behavior of Coagulation: Fenton Combined with MBR Treatment for Pharmaceutical Tail Water - Jian Wang; Chunxiao Zhao; Feng Qian; Jie Su; Hongjie Gao (Molecules)
In this study, the treatment of pharmaceutical tail water (PTW) by coagulation, Fenton combined with membrane bioreactor (MBR), was studied. Optimal parameters were obtained according to batch experiment and central composite design (CCD). Results showed that Polymeric Ferric Sulfate (PFS) was the best coagulant for original pharmaceutical tailwater due to less dosage and higher removal efficiency to TOC, COD, NH4+-N and UV254m, with the optimized pH = 7.25 and 0.53 g/L PFS dosage. The best coagulation performance was achieved when the mixer was stirred at 250 rpm for 3 min, 60 rpm for 10 min, and then left to stand for 60 min. Coagulation mainly removed organics with molecular weight above 10 kDa. After treated by coagulation, 43.1% TOC removal efficiency of PTW was obtained by Fenton reaction with 11.6 mmol/L H2O2, 3.0 mmol/L FeSO4, pH = 3.3 and T = 50 min. A type of common macromolecule aromatic amino acid compounds which located Ex = 250 nm and Em = 500 nm was the main reason that caused the high TOC concentration in the effluent. Stable COD and NH4+-N removal efficiencies in the MBR reactor within 10 d were observed when the mixture of pre-treated PTW (20%, v) and domestic sewage (80%, v) was fed into the MBR reactor, and over 95% COD and 50% NH4+-N were removed. One kind of amino acid similar to tryptophan was the prime reason that caused PTW resistance to be degraded. Analysis of the microorganism community in the MBR suggested that norank_f__Saprospiraceae was the key microorganism in degrading of PTW.